2016
DOI: 10.1007/s00264-016-3261-9
|View full text |Cite
|
Sign up to set email alerts
|

Extra-articular tenodesis combined with an anterior cruciate ligament reconstruction in acute anterior cruciate ligament tear in elite female football players

Abstract: The combination of an LET with ACLR in elite female football players demonstrated excellent results in terms of subjective scales, post-operative residual laxity and re-rupture rate with no complication, and a complete return to sport activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 30 publications
1
26
0
6
Order By: Relevance
“…Furthermore, several systematic reviews have demonstrated that a lateral extra-articular procedure performed at the time of ACLR results in improved knee stability. [15][16][17] This is consistent with the work of Guzzini et al, 18 who reported no graft ruptures and excellent knee stability at medium term follow-up after combined ACLR and lateral extra-articular tenodesis in a high-risk population of 16 elite female soccer players. Although these results are promising, further study is required because of the small study population and the lack of applicability to professional athletes participating in other sports.…”
supporting
confidence: 89%
“…Furthermore, several systematic reviews have demonstrated that a lateral extra-articular procedure performed at the time of ACLR results in improved knee stability. [15][16][17] This is consistent with the work of Guzzini et al, 18 who reported no graft ruptures and excellent knee stability at medium term follow-up after combined ACLR and lateral extra-articular tenodesis in a high-risk population of 16 elite female soccer players. Although these results are promising, further study is required because of the small study population and the lack of applicability to professional athletes participating in other sports.…”
supporting
confidence: 89%
“…23 Similar findings are reported elsewhere. 11,[24][25][26] This study has several limitations: it is a case series with no control group, a small patient sample, and only mid-term follow-up. The retrospective design precludes statistical analysis of strong levels of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 For this reason, lateral extra-articular reconstruction to increase rotational stability has regained popularity in ACL revision in high demand athletes. 11,12 Colombet 13 demonstrated via computer-assisted navigation that lateral extra-articular tenodesis (LET) in combination with ACL revision can improve internal tibial rotation control as compared with isolated intra-articular graft reconstruction. The first LET was described by Lemaire 14 and Ireland and Trickey 15 as surgical treatment for chronic ACL injury to improve stability in rotational laxity of the knee.…”
mentioning
confidence: 99%
“…De los artículos que analizan la tasa de RPD, existen porcentajes bastantes diversos. Mientras que Waldén et al 10 y Guzzini et al 11 confirman una tasa de RPD del 100%, existen porcentajes más bajos tanto en el estudio de Sandon et al 12 como en el de Fältström et al 2 con un 54.1% y un 52% respectivamente. Las tasas de RPD extremidad reconstruida en comparación con la extremidad no afectada, difiriendo sólo mínimamente en algunas pruebas con los jugadores sanos 19 .…”
Section: Resultsunclassified
“…El factor tiempo se analizará desde dos perspectivas: por un lado, el tiempo entre la lesión y la cirugía y, por otro, desde la cirugía al RPD. El primero Fältström et al 2 y Guzzini et al 11 lo consideran un factor importante para el RPD, alegando que las jugadoras en las que este tiempo es de menos de un año tras la lesión tienen una mayor predisposición para completar el RPD. De los artículos de esta revisión actualizada, sólo Zaffagnini et al 16 midieron el período entre la cirugía y el RPD, estimando el regreso al juego en un partido oficial 186 ± 52 días después de la cirugía.…”
Section: Resultsunclassified